Ceramide Kinase Inhibition Blocks IGF-1-Mediated Survival of Otic Neurosensory Progenitors by Impairing AKT Phosphorylation - León, Yolanda; Magariños, Marta; Varela-Nieto, Isabel (Frontiers in Cell and Developmental Biology, 2021)
Sphingolipids are bioactive lipid components of cell membranes with important signal transduction functions in health and disease. Ceramide is the central building block for sphingolipid biosynthesis and is processed to form structurally and functionally distinct sphingolipids. Ceramide can be phosphorylated by ceramide kinase (CERK) to generate ceramide-1-phosphate, a cytoprotective signaling molecule that has been widely studied in multiple tissues and organs, including the developing otocyst. However, little is known about ceramide kinase regulation during inner ear development. Using chicken otocysts, we show that genes for CERK and other enzymes of ceramide metabolism are expressed during the early stages of inner ear development and that CERK is developmentally regulated at the otic vesicle stage. To explore its role in inner ear morphogenesis, we blocked CERK activity in organotypic cultures of otic vesicles with a specific inhibitor. Inhibition of CERK activity impaired proliferation and promoted apoptosis of epithelial otic progenitors. CERK inhibition also compromised neurogenesis of the acoustic-vestibular ganglion. Insulin-like growth factor-1 (IGF-1) is a key factor for proliferation, survival and differentiation in the chicken otocyst. CERK inhibition decreased IGF-1-induced AKT phosphorylation and blocked IGF-1-induced cell survival. Overall, our data suggest that CERK is activated as a central element in the network of anti-apoptotic pro-survival pathways elicited by IGF-1 during early inner ear development.